Voiced or Silent? The Sound of the Sistrum in Ancient Egypt - Tatoń, Katarzyna (Analecta Archaeologica Ressoviensia, 2024)
The sistrum was one of the most popular idiophones of Antiquity and, of all the musical instruments, it was most closely associated with the culture of Ancient Egypt, being present there for most of the time of this civilization’s existence. To this day, numerous examples in a diversity of shapes have remained and their representations also appear on the walls of temples and tombs. They also can be found in statuary sculptures as well as small plastic art. The sound of sistrum was an important element of the cult of varies deities, but primarily that of Hathor. The symbolic function was so strong that the instrument itself became a votive object. Some researchers believe that only the arched sistrum performed a sound purpose, while the faience naos-sistrum supposedly lacked this function. To obtain a more comprehensive picture of the sounds produced by the sistrum, and to evaluate the acoustic capabilities of the naos-sistrum, the experimental approach was employed.